Regression model for predicting tunnel strain in strain-softening rock mass for underground openings. (July 2019) - Cui, Lan; Sheng, Qian; Zheng, Jun-jie; Cui, Zhen; Wang, An; Shen, Qiang
Abstract: Regression analysis method has been extensively used to predict tunnel during excavations. This paper applies the method to solve for the tunnel strain for a circular opening in a strain-softening rock mass. Support pressure, in-situ stress and geological strength index (GSI) are three important geological parameters that are simultaneously considered in evaluating tunnel strain. A numerical procedure of the strain-softening rock mass is incorporated to solve for tunnel strain with a series of GSI, in-situ stress and support pressure. A detailed result of the tunnel strain is solved using the repeated numerical procedures. A nonlinear regression model for predicting tunnel strain is obtained through analysing the result with the regression method. Twelve fitting equations are considered in the regression model, correlating the tunnel strain with the support pressure, GSI, initial stress and critical softening parameters. The analysis framework is validated by comparing the calculated tunnel strain to that predicted by existing studies. The influence of the critical softening parameter on tunnel strain and the radius of the plastic zone are investigated. The response surfaces of tunnel strain versus the initial stress and support pressures for different rock mass qualities with various softening behaviours are also analysed. Then a guidance of the support design is derived based on the regression model and is demonstrated in an actual tunnel case with field measurements.